MODEL OF GREEN TOURISM DESTINATION AT NUSA LEMBONGAN, KLUNGKUNG REGENCY, BALI PROVINCE - A.A.Ayu Ngurah Harmini (Journal of Business on Hospitality and Tourism, 2016)
This research was conducted in the area of Nusa Lembongan district, at Klungkung regency with the specifications of the main potential is nautical. The purpose of this research is to determine the characteristics of the tourist attractions in Nusa Lembongan and also to design a model of green tourism destination. The data collection is done by observation, interview, and literature.The analysis technique used is descriptive qualitative research that seeks to describe and illustrate the relationship between the phenomenon or phenomena studied by systematic, factual and accurate. From the discussion, it can be described that tourism development today is more directed to the development of green tourism rather than conventional tourism. To make this happen, the authors will try to design a model of the development of green tourism destination in Nusa Lembongan. Based on the above motivations there are three factors that play an important role in supporting green tourism destination, namely: green tourist, green area (object and attraction) , and information about the area. Therefore by the next implication, every object and attraction developed are expected to follow the model of the development of green tourism for Nusa Lembongan because Nusa Lembongan only suitable as a green tourism destination.